Gender, Institutions and Political Representation Reproducing Male Dominance in Europe's New Democracies - Chiva, Cristina (Gender and Politics,, 2018)
This book traces the struggles over the institutions of political representation in Central and Eastern Europe, focusing on the factors that have held women back over the post-communist period, as well as on the growing evidence for change throughout the region. Post-communist Europe has long raised two puzzles for scholars of women's representation in politics. First, why have women been under-represented in politics in every country in the region since communism's collapse? Secondly, why are there relatively few cases where women's advocates have been successful in pressing for change? This comparative study of Europe's new democracies argues that these puzzles are best understood as questions about male dominance - that is, about the mechanisms that sustain, or, alternatively, change long-established patterns of male over-representation in politics over time. The author covers six EU member states - Bulgaria, the Czech Republic, Hungary, Poland, Romania and Slovakia - during the period 1990-2016. The book will be of use to students and scholars in the fields of Comparative Politics, Democracy and Democratization, European Studies, Gender Studies, Post-Communist Studies, and Central and Eastern European Studies.